Substrate and Transition State Binding in Alkaline Phosphatase Analyzed by Computation of Oxygen Isotope Effects - Roston, Daniel (J Am Chem Soc, 2016)
Enzymes are powerful catalysts and a thorough understanding of the sources of their catalytic power will facilitate many medical and industrial applications. Here we have studied the catalytic mechanism of alkaline phosphatase (AP), which is one of the most catalytically proficient enzymes known. We have used quantum mechanics calculations and hybrid quantum mechanics/molecular mechanics (QM/MM) simulations to model a variety of isotope effects relevant to the reaction of AP. We have calculated equilibrium isotope effects (EIEs), binding isotope effects (BIEs), and kinetic isotope effects (KIEs) for a range of phosphate mono- and diester substrates. The results agree well with experimental values, but the model for the reaction’s transition state (TS) differs from the original interpretation of those experiments. Our model indicates that isotope effects on binding make important contributions to measured KIEs on V/K, which complicated interpretation of the measured values. Our results provide a detailed interpretation of the measured isotope effects and make predictions that can test the proposed model. The model indicates that the substrate is deformed in the ground state (GS) of the reaction and partially resembles the TS. The highly preorganized active site preferentially binds conformations that resemble the TS and not the GS, which induces the substrate to adapt to the enzyme, rather than the other way around—as with classic “induced fit” models. The preferential stabilization of the TS over the GS is what lowers the barrier to the chemical step.